PENERAPAN PEMBELAJARAN INQUIRY CYCLE UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF DAN SCIENTIFIC REASONING SISWA SMA KELAS X PADA MATERI GERAK HARMONIK SEDERHANA - Hadianti, Dini (2017)
This study aims to get an overview of cognitive abilities, scientific reasoning, the relationship between cognitive ability and scientific reasoning, and student responses as a result of the application of inquiry cycle learning on simple harmonic motion. The research method used is quasi experiment and descriptive with the randomized pretest-posttest control group design. The sample of the study consisted of 63 students of grade X in one high school in Kab. Pandeglang. Inquiry cycle learning refers to inquiry learning developed by Pedaste, and scientific reasoning capabilities developed by Furtak. Based on the analysis conducted, cognitive ability of the experimental class was more increased with normalized average gain values < ḡ > is 0.46 than the normalized gain value of < ḡ > control class is 0.2. Likewise, the scientific reasoning of ability experimental class is more improved with the normalized average gain value < ḡ > is 0.39 than the normalized average gain value < ḡ > control class is 0.23. The relationship between cognitive ability with scientific reasoning has a positive correlation with correlation coefficient is 0.430. In its application, most students have positive responses to inquiry cycle learning.---- Penelitian ini bertujuan untuk mendapatkan gambaran peningkatan kemampuan kognitif, scientific reasoning, hubungan antara kemampuan kognitif dan scientific reasoning, dan tanggapan siswa sebagai akibat penerapan pembelajaran inquiry cycle pada materi gerak harmonik sederhana. Metode penelitian yang digunakan adalah kuasi eksperimen dan deskriptif dengan the randomized pretest-posttest control group design. Sampel penelitian terdiri atas 63 siswa kelas X di salah satu SMA di Kab. Pandeglang. Pembelajaran inquiry cycle mengacu pada pembelajaran inkuiri yang dikembangkan oleh Pedaste, dan kemampuan scientific reasoning yang dikembangkan oleh Furtak. Berdasarkan analisis yang dilakukan, kemampuan kognitif kelas eksperimen lebih mengalami peningkatan dengan nilai rata-rata gain yang ternormalisasi < ḡ > sebesar 0.46 dari pada nilai rata-rata gain yang ternormalisasi < ḡ > kelas kontrol sebesar 0.2. Begitu juga kemampuan scientific reasoning lebih mengalami peningkatan dengan nilai rata-rata gain yang ternormalisasi < ḡ > kelas eksperimen sebesar 0.39 dari pada nilai rata-rata gain yang ternormalisasi < ḡ > kelas kontrol sebesar 0.23. Hubungan antara kemampuan kognitif dengan scientific reasoning memiliki korelasi positif dengan koefisien korelasi 0.430. Dalam penerapannya, sebagian besar siswa memiliki tanggapan positif terhadap pembelajaran inquiry cycle.